ANALISIS KEMAMPUAN KONEKSI MATEMATIS : DAMPAK LASSWELL COMMUNICATION BERBASIS PEMECAHAN MASALAH DAN KEPRIBADIAN KEIRSEY - Indah Resti Ayuni Suri; Ruhban Masykur; Ramayudha Dwi Aji G. (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2021)
This research has objectives, including analyzing the influence of the Lasswell Communication Model based on problem-solving and Keirsey's personality on the ability of mathematical connections. And to investigate the interaction between the Lasswell Communication Model based on problem-solving and Keirsey personality to the mathematical connection ability. Researchers will apply some action or treatment in this study using Quasi-experiments. The sampling technique is a technique used in selecting a sample